Comparison Effectiveness of Concrete and Digital Mathematics Learning Media: Systematic Literature Review on Industrial Revolution 4.0 Era - Pulungsari, Mohamad Wegik; Hidayah, Isti (Journal of Education Method and Learning Strategy, 2024)
Industrial Revolution 4. 0. Technological developments affect all aspects of human life, as well as education. Therefore, innovation is needed to achieve learning objectives. The goal is to produce a competitive workforce equipped with skills known as the 4Cs (communication, collaboration, critical thinking and problem solving, creativity and innovation). Reforms in the field of mathematics education to achieve the intended expectations include the use of tangible digital educational media. Researchers conducted research using systematic literature review methods to find out the latest facts about concrete and digital mathematics learning media in the era of the Industrial Revolution 4. 0. We interpret a total of 30 articles from various databases and make an overview of the use, advantages and disadvantages of digital and real mathematics educational media in the era of the Industrial Revolution 4. 0. The benefits of real educational media include improving students' problem-solving, creative and thinking skills, and visual reasoning. The advantages of digital learning media include efficiency and efficiency when learning mathematics, allowing for face-to-face (distance) learning, and eliminating the need for certain treatments. The shortcomings of concrete learning media require more consideration so that it takes a long time.